Organizational complexity and audit report lag in GCC economies: the moderating role of audit quality - Khan, Faisal; Abdul-Hamid, Mohamad Ali; Fauzi Saidin, Saidatunur; Hussain, Shatha (Emerald, 2023)
Purpose This study aims to investigate whether organizational complexity (hereafter firm complexity) increases audit report lag (ARL) in a unique environment of GCC countries.